Precision Agriculture Technology: Accelerating Sustainable Food Security and Resource Efficiency - Yudi Garnida (Journal Of Data Science, 2026)
The global agricultural sector currently faces significant challenges in the form of surging food demand amidst environmental degradation due to global climate change. This study aims to analyze the role of precision agriculture technology in accelerating the realization of sustainable food security while optimizing the efficiency of resource use (water, fertilizer, and land). The method used was a qualitative descriptive approach through a literature review of various national and international scientific articles, textbooks, and official reports from relevant agencies for the 2021–2026 period. The results show that the integration of a digital ecosystem based on the Internet of Things (IoT), automatic sensors, drones, and artificial intelligence (AI) can transform production patterns into data-driven farming, boosting crop productivity by 20–30%. Through a variable-dose application system, this technology has also successfully reduced irrigation water and chemical fertilizer use by 15–25%, minimizing negative ecological impacts. However, this massive potential is hampered by structural issues among local farmers, such as high initial capital requirements, fragmented land use, the demographic digital literacy gap, and fragile rural connectivity. This study concludes that democratizing precision agriculture requires inclusive public policy interventions through farmer corporation consolidation programs, smart fiscal stimulus, strengthening the upstream internet, and implementing the Agriculture-as-a-Service (AaaS) business model.